The effect of ranger patrols on the sighting of large mammals by local herders in Northern Iran - Farid Salmanpour; Zahra Shakoori; Mahan Salmanpour; Mehdi Tizrouyan; Mehdi Kia; Rahman Eshaghi; Saeid Ghomi; Abolfazl Rahbarizadeh; Rahman Naeimaei; Mehdi Ghaderi (Heliyon)
Ranger patrols are essential for biodiversity conservation, particularly in protected areas where they help mitigate poaching of large mammals. Effective patrols reduce poaching and support higher population densities of large mammals. This study investigates the impact of ranger patrols on large mammal sightings in the Central Alborz Protected Area (CAPA), northern Iran, a crucial wildlife corridor with UNESCO-listed Hyrcanian forests and high-altitude grasslands. CAPA also supports livestock grazing in over 200 villages, making it a key area for studying human-wildlife interactions. Data were gathered using semi-structured questionnaires from local herders, whose observations provide valuable insights into wildlife presence and the effectiveness of ranger patrols. The study area was divided into 5 × 5 km grid cells to ensure uniform data collection. Results show that large mammal sightings decrease with increasing distance from active, semi-active, and seasonal ranger stations. This trend is likely due to reduced patrol coverage, which increases poaching risks. Although factors such as habitat preferences and human disturbances may contribute. Inactive ranger stations appear to have lost effectiveness, likely because of the lack of regular patrols, which warrants further investigation. These findings emphasize the critical role of consistent patrol efforts in reducing poaching and maintaining wildlife populations in this ecologically important region.